Tingkat Kecemasan Meningkatkan Risiko Tension Type Headache pada Mahasiswa Kedokteran - Riyadh Anugrah Mardiana Riyadh; Meta Maulida; Herri S. Sastramihardja (UNISBA Press, 2023)
Abstract. Anxiety is one of the most common psychiatric disorders. The anxiety experienced by medical students occurs because of differences in curriculum methods, independent learning and achieving learning targets for each block, extracurricular activities and competition between students. This can trigger excessive anxiety which can cause a tension type headache. The purpose of this study was to determine the relationship between anxiety levels and tension type headache (TTH) in students at the academic stage of the Unisba Medical Faculty in 2022/2023. This type of research is analytic observational with a cross sectional design. Sampling was done by random sampling technique. Anxiety was diagnosed using the validated Hamilton Rating Scale for Anxiety questionnaire. The diagnosis of TTH is based on the Headache Screening Questionnaire-Dutch Version (HSQ-DV) according to the International Classification of Headache Disorder. The relationship between these variables was analyzed using the Chi-square test. The results of the study obtained 90 samples with the majority of 77 students having a mild level of anxiety with 71 of them not experiencing TTH. The results of the Chi-square test showed a significant relationship between anxiety and tension type headache with a value of p = 0.000 (p≤0.05). This shows that the level of anxiety can cause tension type headaches. The higher the level of anxiety, the greater the possibility of a tension type headache. Abstrak. Kecemasan merupakan salah satu kelompok gangguan kejiwaan yang sangat umum. Kecemasan yang dialami mahasiswa kedokteran terjadi karena perbedaan metode kurikulum, belajar mandiri dan mencapai target pembelajaran setiap bloknya, aktivitas ekstrakurikular dan persaingan antarmahasiswa. Hal ini dapat memicu timbulnya kecemasan yang berlebih yang dapat menyebabkan tension type headache. Tujuan dari penelitian ini adalah untuk mengetahui hubungan tingkat kecemasan dan tension type headache (TTH) pada mahasiswa tahap akademik Fakultas Kedokteran Unisba Tahun 2022/2023. Jenis penelitian ini adalah observasional analitik dengan rancangan cross sectional. Pengambilan sampel dilakukan dengan teknik random sampling. Kecemasan didiagnosis dengan menggunakan kuesioner Hamilton Rating Scale for Anxiety yang telah divalidasi. Diagnosis TTH berdasarkan Headache Screening Questionnaire-Dutch Version (HSQ-DV) yang sesuai dengan International Classification of Headache Disorder. Hubungan antar variabel tersebut dianalisis dengan menggunakan uji Chi-square. Hasil penelitian didapatkan 90 sampel dengan mayoritas 77 mahasiswa yang memiliki tingkat kecemasan ringan dengan 71 mahasiswa diantaranya tidak mengalami TTH. Hasil uji Chi-square menunjukkan hubungan yang bermakna antara kecemasan dengan tension type headache dengan diperoleh nilai p= 0,000 (p≤0.05). Hal ini menunjukkan bahwa tingkat kecemasan dapat menyebabkan timbulnya tension type headache. Semakin tinggi tingkat kecemasan, semakin besar kemungkinan terjadinya tension type headache.